2016
DOI: 10.1063/1.4960987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humoral immunity on HIV-1 dynamics with virus-to-target and infected-to-target infections

Abstract: We consider an HIV-1 dynamics model by incorporating (i) two routes of infection via, respectively, binding of a virus to a receptor on the surface of a target cell to start genetic reactions (virus-to-target infection), and the direct transmission from infected cells to uninfected cells through the concept of virological synapse in vivo (infected-to-target infection); (ii) two types of distributed-time delays to describe the time between the virus or infected cell contacts an uninfected CD4+ T cell and the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our model can be adapted for HBV infection, and the above result can also explain the dysfunction of the adaptive immune response in patients infected with HBV, which is still largely incomplete [33]. Furthermore, the model and the results presented in this study improve and generalize the models and the corresponding results in more recent papers with only cellular immunity [5], with only humoral immunity [6][7][8][9], and with both arms of immunity [15,17].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our model can be adapted for HBV infection, and the above result can also explain the dysfunction of the adaptive immune response in patients infected with HBV, which is still largely incomplete [33]. Furthermore, the model and the results presented in this study improve and generalize the models and the corresponding results in more recent papers with only cellular immunity [5], with only humoral immunity [6][7][8][9], and with both arms of immunity [15,17].…”
Section: Discussionsupporting
confidence: 57%
“…In 2016, Wang et al [5] improved the model given by Equation (2) by considering the role of cellular immune response. In the same year, Elaiw et al [6] improved the model given by Equation (2) by considering only the role of humoral immune response and infinite distributed delay in virus production. In 2017, Lin et al [7] improved the models of Wang and Zou [8] and Murase et al [9] by incorporating both modes of transmission, intracellular delay and humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these works the antibody immune response was neglected. In very recent works [34,35], and [36], both pathogen-to-susceptible and infected-to-susceptible transmissions were incorporated in the pathogen dynamics models with antibody immune response. However, the latently infected cells were neglected in these models.…”
Section: Introductionmentioning
confidence: 99%
“…All the aforementioned works assume that the uninfected cells becomes infected because of virus contacts. Recently, it has been reported that the uninfected cells can also become infected because of direct contact with infected cells . The viral infection model with cell‐to‐cell transmission and distributed time delay has been proposed in as a nonlinear system with integral delay terms: trueṪ(t)=ρdT(t)β1T(t)V(t)β2T(t)T(t), trueṪ(t)=0ψ1(s)eδ1s[]β1T(ts)V(ts)+β2T(ts)T(ts)dsμT(t), trueV̇(t)=b0ψ2(s)eδ2sT(ts)dscV(t), where T ( t ), T ∗ ( t ), and V ( t ) are the concentrations (the number of cells or viruses per unit volume) of the uninfected uninfected cells, infected cells, and free virus particles at time t , respectively.…”
Section: Introductionmentioning
confidence: 99%